Enzymatic browning control by combined citric acid and ascorbic acid treatment of organically grown leaf lettuce - Ranot, Ma. Angela Picones (2007)
ABSTRACT The effects of combined citric acid (CA) and ascorbic acid (AA) treatments for enzymatic browning control of organically grown leaf lettuce lettuce (Lactuca sativa Linn.) were investigated. Fresh organic lettuces were minimally processed into cut leaf pieces and immersed in 0.10%, 0.20% and 0.30% CA, each with 100 ppm AA for 2 minutes and air dried. Changes on CIE L*, a*, b*, h*, ΔE*and chroma and on pH and titratable acidity of control and treated samples stored at 9±1°C for 8 days were investigated. Based on these, combined 0.10% CA and 100 ppm AA was selected as the test treatment for control of browning discoloration on cut lettuce. During the second phase, samples subjected to this level of combined CA-AA treatment were assessed for microbiological and sensory qualities during storage. This treatment caused slight reduction on aerobic plate count of organically-produced lettuce but population rose gradually during storage. Yeast and mold count were generally maintained throughout the storage period, while coliform count exceeded the reported allowable count for minimally processed produce. However, no E. coli was detected in all samples. Lettuce sensory attributes such as color and texture had lower scores and acceptance ratings dislike of "dislike moderately" by the end of storage